Reverse Shoulder Arthroplasty: Perioperative Considerations and Complications. Issue 8 (August 2018) - Jauregui, Julio J.; Nadarajah, Vidushan; Shield, William P.; Henn, R. Frank; Gilotra, Mohit; Hasan, S. Ashfaq
Abstract : The most common indication for reverse total shoulder arthroplasty is primary rotator cuff tear arthropathy. Indications for reverse total shoulder arthroplasty have expanded beyond rotator cuff tear arthropathy to include other pathologies such as irreparable rotator cuff tears, glenohumeral arthritis with an intact rotator cuff, acute proximal humeral fractures, the sequelae of proximal humeral fractures, neoplasms of the proximal part of the humerus, inflammatory arthropathies, and failed total shoulder arthroplasty and hemiarthroplasty. Reverse total shoulder arthroplasty continues to have high rates of complications, which include instability, infection, scapular notching, neurologic injury, and component loosening, among others.